Exploring the Risk-Taking Behavior of Student Athletes While Attending Education on Campus - Miftakhul Jannah; Nurchayati Nurchayati; Diana Rahmasari; Damajanti Kusuma Dewi; Rachman Widohardhono (International Journal of Current Educational Research, 2022)
Every student who attends lectures on campus is expected to have achievements as an academic member. This also applies to student-athletes excelling in sports and balancing it with academic achievement. Achievement is related to athletes' physical abilities and skills in performing techniques. The high level of physical activity that is carried out requires athletes' involvement in taking risks both during training and competitions. This study aims to determine the profile of risk-taking behavior in Surabaya State University students. A total of 230 student-athletes became the subject of the study, with an age range of 19-24 years, with 35 people in the categories of accuracy sports, 57 people in Pencak silat, 96 people in games, and 42 people in the competition. The instrument used is risk-taking behavior—data analysis techniques using descriptive statistics. The data analysis tool used the Jeffreys' Amazing Statistics Program (JASP) application version 0.14.1.0. The data analysis results showed that most subjects' risk-taking behavior was at a good level of 157 people or 86.3 percent. The dominant risk-taking behavior is at a high level of 73 people or 31.73 percent at a moderate level. The implications of this research are the data for campuses to promote sports activities so that students have good risk-taking behavior. Through good decision-making behavior, it is hoped that it will encourage the achievement of student-athlete's academic and sports achievements.